DNA methylation alteration is a major consequence of genome doubling in autotetraploid Brassica rapa - Xu, Yanhao; Zhang, Wenying; Chen, Gonghai; Wang, Jianbo (Archives of Biological Sciences, 2017)
Polyploids are typically classified as autopolyploids or allopolyploids based on the origin of their chromosome sets. Autopolyploidy is much more common than traditionally believed. Allopolyploidization, accompanied by genomic and transcriptomic changes, has been well investigated. In this study, genetic, DNA methylation and gene expression changes in autotetraploid Brassica rapa were investigated. No genetic alteration was detected using an amplified fragment length polymorphism (AFLP) approach. Using a cDNA-AFLP approach, approximately 0.58% of fragments showed changes in gene expression in autotetraploid B. rapa. The methylation-sensitive amplification polymorphism (MSAP) analysis showed that approximately 1.7% of the fragments underwent DNA methylation changes upon genome doubling, with hypermethylation and demethylation changes equally affected. Fragments displaying changes in gene expression and methylation status were isolated and then sequenced and characterized, respectively. This study showed that variation in cytosine methylation is a major consequence of genome doubling in autotetraploid Brassica rapa. https://doi.org/10.2298/ABS170131015X Received: January 31, 2017; Revised: April 6, 2017; Accepted: May 4, 2017; Published online: May 23, 2017 How to cite this article: Xu Y, Zhang W, Chen G, Wang J. DNA methylation alteration is a major consequence of genome doubling in autotetraploid Brassica rapa. Arch Biol Sci. 2017;69(4):689-97.